2024
DOI: 10.1002/wps.21176
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and cost‐effectiveness of online recorded recovery narratives in improving quality of life for people with non‐psychotic mental health problems: a pragmatic randomized controlled trial

Mike Slade,
Stefan Rennick‐Egglestone,
Rachel A. Elliott
et al.

Abstract: Narratives describing first‐hand experiences of recovery from mental health problems are widely available. Emerging evidence suggests that engaging with mental health recovery narratives can benefit people experiencing mental health problems, but no randomized controlled trial has been conducted as yet. We developed the Narrative Experiences Online (NEON) Intervention, a web application providing self‐guided and recommender systems access to a collection of recorded mental health recovery narratives (n=659). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The NEON-O Trial included participants who experienced mental health problems other than psychosis in the last 5 years ( N = 1,023, https://www.isrctn.com/ISRCTN63197153 ). It found that NEON Intervention access was effective at increasing quality of life, increasing the presence of meaning in life, and was cost-effective from the perspective of the statutory health and social care system in England ( 30 ). The NEON Trial ( N = 739, https://www.isrctn.com/ISRCTN11152837 ) included participants experiencing current mental health distress, and who had experienced psychosis in the last 5 years.…”
Section: Introductionmentioning
confidence: 99%
“…The NEON-O Trial included participants who experienced mental health problems other than psychosis in the last 5 years ( N = 1,023, https://www.isrctn.com/ISRCTN63197153 ). It found that NEON Intervention access was effective at increasing quality of life, increasing the presence of meaning in life, and was cost-effective from the perspective of the statutory health and social care system in England ( 30 ). The NEON Trial ( N = 739, https://www.isrctn.com/ISRCTN11152837 ) included participants experiencing current mental health distress, and who had experienced psychosis in the last 5 years.…”
Section: Introductionmentioning
confidence: 99%